THE DAXIANGGUO TEMPLE BUDDHIST ORCHESTRA OF CHINA: CONTEMPORARY ROLE AND FUNCTIONS (Proceeding of the International Conference on Arts and Humanities, 2024)
The Daxiangguo Temple is located in Kaifeng City, Henan Province, China, and the center of the ancient capital of the Seven Dynasties. Because of its status as a royal temple, the Buddhist orchestra was involved in several imperial events with a long history and profound cultural heritage. Since July 2002, the Daxiangguo Temple Buddhist Orchestra (DTBO) has been rebuilt. 2007, the DTBO acquired the second national intangible cultural heritage project batch. The author investigates the DTBO in recent years, through ethnographic writing, about the operation of the orchestra in the last 20 years, the content of its performances, and investigates its current situation in terms of cultural inheritance and seeking development after its successful declaration as a national intangible cultural heritage project. Research shows that the DTBO plays an essential role in preserving traditional Chinese music culture and propagating religious beliefs and ethical ideas in modern society. The local government displayed it as a cultural symbol of the Central Plains. The preservation and continuation of cultural genes strengthen the religious consciousness of believers and the sense of belonging and cultural identity of the Central Plains people.
Keywords: buddhist music; instrument orchestra; national-policies; cultural symbols; self-identify